The formation of optimal portfolio - the evidence of Malaysia shariah compliant securities / Nor Hazila Ismail and Yuslizawati Mohd Yusof - Ismail, Nor Hazila; Mohd Yusof, Yuslizawati (2010)
This study is conducted to identify the optimal formation of portfolio based on the selected shariah compliant stocks. Portfolio investment is a combination of many securities or asset where an investor needs to consider many things in selecting the best combination of asset to be included into the portfolio. This study attempt to identify which stocks should be included in the portfolio in order to reduce the effect of measurement error on optimal portfolio allocations as well as to calculate the percentage that investors should invest in each security to ensure the investor able to optimize their returns. The method applied here is based on Simple Sharpe Portfolio Optimization. The study covered the period of 1997 to 2009 in order to see the different formation of portfolio before the 1997 crisis and 2007 crisis.